Derivation of risk indices and analysis of variablility for the management of incidents involving the transport of nuclear materials in the Northern Seas. (15th April 2016) - Brown, J.; Hosseini, A.; Karcher, M.; Kauker, F.; Dowdall, M.; Schnur, R.; Strand, P.
Abstract: The transport of nuclear or radioactive materials and the presence of nuclear powered vessels pose risks to the Northern Seas in terms of potential impacts to man and environment as well socio-economic impacts. Management of incidents involving actual or potential releases to the marine environment are potentially difficult due to the complexity of the environment into which the release may occur and difficulties in quantifying risk to both man and environment. In order to address this, a state of the art oceanographic model was used to characterize the underlying variability for a specific radionuclide release scenario. The resultant probabilistic data were used as inputs to transfer and dose models providing an indication of potential impacts for man and environment This characterization was then employed to facilitate a rapid means of quantifying risk to man and the environment that included and addressed this variability. The radionuclide specific risk indices derived can be applied by simply multiplying the reported values by the magnitude of the source term and thereafter summing over all radionuclides to provide an indication of total risk. Highlights: The variability of oceanic transport pathways was assessed. A system for calculating risk indices for radioactive contaminants was described. The incorporation of variability within the system was explored.